Feasibility of Motor Imagery Training for Children with Developmental Coordination Disorder – A Pilot Study - Adams, Imke L. J.; Smits-Engelsman, Bouwien; Lust, Jessica M.; Wilson, Peter H.; Steenbergen, Bert (Frontiers in Psychology, 2017)
Children with Developmental Coordination Disorder (DCD) experience movement difficulties that may be linked to processes involved in motor imagery (MI). This paper discusses recent advances in theory that underpin the use of motor imagery (MI) training for children with Developmental Coordination Disorder (DCD). This knowledge is translated in a new MI training protocol which is compared with the Cognitive Orientation to daily Occupational Performance (CO-OP). Children meeting DSM-5 criteria for DCD were assigned to MI (n=4) or CO-OP (n=4) interventions and completed 9 treatment sessions, including homework exercises. Results were positive, with two children in the MI group and three in the CO-OP group improving their m-ABC-2 score by ≥ 2 standard scores, interpreted as a clinically meaningful change. Moreover, all children and parents noticed improvements in motor skills after training. This is the first study to demonstrate the feasibility of a theoretically principled treatment protocol for MI training in children with DCD, and extends earlier work.